Teleost Fish and Organoids: Alternative Windows Into the Development of Healthy and Diseased Brains - Fasano, Giulia; Compagnucci, Claudia; Dallapiccola, Bruno; Tartaglia, Marco; Lauri, Antonella (Frontiers in Molecular Neuroscience, 2022)
The variety in the display of animals’ cognition, emotions, and behaviors, unique in humans, has its roots within the anterior-most part of the brain, the forebrain. Our understanding of cellular and molecular events instructing the development of this special domain and its multiple functional adaptations has rapidly progressed in the last decade thanks to technical advances in genetics, evo-devo, and neuroscience. Expanding and detailing the available survey of the fundamental processes from progenitors’ cell behavior to complex CNS patterning and functional sophistication is key also to improving diagnosis of etiologically heterogeneous neurodevelopmental conditions, largely caused by severe and mechanistically unexplored cortical malformations. Classical and emerging mammalian and non-primate models are unreplaceable to accurately elucidate stem cells expansion mechanisms and possible impairments occurring during cortex development. Nevertheless, simpler and convenient vertebrates, as well as patients-derived in vitro 2D and 3D models for studying the basic strategies of neural stem cells biology and morphogenesis are being accepted within large translational workflows spanning from genetic analysis to functional investigations. These approaches provide valuable comparative insights into brain development and evolution and ultimately refine disease classification and management. Here, we briefly review the current knowledge of common and divergent mechanisms shaping the forebrain in vertebrates and causing cortical malformations in humans. We specifically address the utility, benefits, and limitations of whole-brain/organism-based fish models and neuronal ensembles in vitro, including those recreated from pediatric patients, for a rationalized translational roadmap to unravel key genes and pathological mechanisms involved in neurodevelopmental diseases.